ANALYSIS OF BLOOD PROTEIN LEVELS IN LONG-DISTANCE RUNNERS AFTER LOW-INTENSITY AEROBIC EXERCISE - Shatha Hazim Horgees Hana (Universitas Negeri Jakarta, 2025)
Background. Serum proteins as factors of the physiological adaptation and metabolic regulation in endurance athletes. Yet, the acute effects of low-intensity aerobic exercise on circulatory protein biomarkers remain less investigated among LDRs. Objectives. The objective of this study was to compare the serum levels of proteins (albumin, globulins, and fibrinogen) before and after low-intensity aerobic exercise in long-distance runners. Method. The sample was composed of 6 purposively selected runners from the Nineveh national team (60% of the total number). Venous blood samples were obtained before and after a standardized low-intensity aerobic exercise. Serum protein levels The serum protein levels were determined by standard biochemical methods. Statistical analysis were performed with using ARITH average, SD standard devitation, 2 paired t- test and TCV cioifficient of variation. SPSS version 11.0 was used for the statistical analysis. Results. There were no significant changes on serum albumin and fibrinogen with low-intensity aerobic exercise (p > 0.05). By contrast, serum globulin levels did not significantly change. These results demonstrate selective physiological changes in blood protein response to aerobic low intensity loading in endurance trained athletes. Conclusion. In response to low intensity physical activity there are marked changes of certain serum proteins (above all those of albumin and fibrinogen), while globulins do not change significantly. These data indicate that acute oxygen costs have an effect on some biochemical hydration, inflammation and metabolic markers. The present study adds to the knowledge of acute biochemical effects of low-intensity aerobic activity in athletes with endurance intensity. The results lay the groundwork for serum protein dynamics-based load training load optimization. Future work should use larger populations, differentiate between male and female athletes, differentiate training intensities and durations to increase the explanatory power of this biomarker analysis for sports performance and recovery in future studies.